Adaptasi Komunikasi Internal Berbasis Nilai Islam pada Organisasi Nirlaba di Era Kerja Hibrida: Sebuah Tinjauan Literatur Integratif - Syukri, Sarah; Tarigan, Muhammad Iqbal Suranta (Salam (Islamic Economics Journal), 2026)
The post-pandemic adoption of hybrid work models presents a paradoxical challenge for Islamic faith-based non-profit organizations: increased digital connectivity coincides with the erosion of social cohesion and employee emotional attachment. This study aims to construct a communication adaptation strategy framework capable of bridging technological efficiency with the preservation of organizational spiritual values. Using an Integrative Literature Review method, this study synthesizes theoretical and empirical literature published between 2019 and 2025. The analysis reveals that the lack of non-verbal cues in computer-mediated communication triggers "digital fatigue" and trust deficits, threatening team militancy. As a solution, this research proposes a "Value-Based Resilient Communication Model" anchored on two pillars: (1) Information Integrity through the institutionalization of Tabayyun (verification) and Qaulan Sadida (straight speech) protocols to mitigate role ambiguity ; and (2) Digital Interaction Humanization through the application of Qaulan Layyina (gentle speech) in empathetic leadership to nurture Ukhuwah (brotherhood). In conclusion, communication adaptation in Islamic organizations is not merely a technical transformation, but an integration of prophetic ethics that positions technology as a means to strengthen heart-to-heart bonds, rather than just an instructional tool